Soil water regime of grassland communities along subtle topographic gradient in the flooding Pampa (Argentina) - Di Bella, Carla Estefanía (2016)
Fil: Di Bella, Carla Estefanía. Universidad de Buenos Aires. Facultad de Agronomía. Instituto de Investigaciones Fisiológicas y Ecológicas Vinculadas a la Agricultura (IFEVA). Buenos Aires, Argentina.